Evaluation of regional urbanisation policy Case study: Bandar Tenggara / Ahmad Hj. Abd. Majid - Hj. Abd Majid, Ahmad (1982)
Regional Development has been regarded as one of the main strategies to achieve the National Economic Policy (NEF) in the Second Malaysia Plan. The two pronged objectives of NEP are the eradiction of poverty irrespective of race and the restructuring of society which gradually eliminate the identification of race with economic functions. The poor or low socio-economic condition of the rural populations are the main determinants of the rural urban migration. In the pre and post independent periods, massive rural urban migrations took place due to economic disparities between regions, racial and certain occupational groups. In the Second Malaysia Flan, several measures have been taken to tackle the socio economic development of the poor regions and rural populations of urban Halays pre-dominate. The concept of rural new towns development in the resource frontier regions of the less developed east coast states has been adopted and being carried out. The main aims of the rural new town developments are on the regional urbanisations policy and concept as to upgrade the socio economic well beings of the rural populations in making transitions to the urban way of life.